L’identité nationale canadienne au travers des affiches de propagande des Première et Seconde Guerres mondiales - Jean Quellien; Andrew Ives (Revue LISA)
War posters often call upon a series of symbols and personifications of the nation in order to spark the citizen’s sense of patriotic duty. In the case of Canada, the propaganda posters produced during the two world wars allow us to study the creation process for this common register of symbols. On one level, the posters illustrate the movement from the status of dominion within the Empire to that of independent nation. This change in status obliged the country to invent a series of national symbols, and to discard the First World War strategy of appealing to isolated groups of citizens according to their ethnic or cultural origins. The Second World War posters reveal the federal government’s plan to create a new pan-Canadian nationalism, a process that would continue into the 1960s.